2000
DOI: 10.1055/s-2000-9330
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Perioperative Lumbar Cerebrospinal Fluid Pressure in Patients Undergoing Acoustic Neuroma Surgery

Abstract: An important complication of acoustic neuroma surgery is the development of a CSF fistula. A fistula is a potentially life-threatening complication and results in a fivefold increase in the incidence of meningitis.' The incidence of CSF rhinorrhea or CSF leakage from the wound is approximately 15% in most major series and does not differ significantly between the translabyrinthine and retrosigmoid (suboccipital) approaches.The usual path of CSF rhinorrhea following translabyrinthine surgery is from the posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…We suggest, therefore, that there may be a unifying organic basis to many of the complex symptoms and problems following skull base surgery, including headache and CSF leaks, in the form of iatrogenic compromise to cranial venous outflow. Moreover, we suggest that a CSF leak represents a pathological, but essentially homeostatic, response to raised intracranial pressure in this situation and that while meticulous surgical technique may reduce its incidence, 14 if cranial venous outflow compromise is left untreated, this may simply mean that one set of symptoms are exchanged for another. 37…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We suggest, therefore, that there may be a unifying organic basis to many of the complex symptoms and problems following skull base surgery, including headache and CSF leaks, in the form of iatrogenic compromise to cranial venous outflow. Moreover, we suggest that a CSF leak represents a pathological, but essentially homeostatic, response to raised intracranial pressure in this situation and that while meticulous surgical technique may reduce its incidence, 14 if cranial venous outflow compromise is left untreated, this may simply mean that one set of symptoms are exchanged for another. 37…”
Section: Discussionmentioning
confidence: 98%
“…[11][12][13] One could speculate further that a similar mechanism might apply in patients who show no hydrocephalus preoperatively, the underlying problem eventually declaring itself as delayed healing of an iatrogenic dural defect. 14 We have seen narrowing of the sigmoid sinus where it crosses the craniectomy defect following vestibular schwannoma surgery and published a report in which repair of this narrowing by stenting brought about resolution of postoperative headache. 15 Similarly, we have published a report in which jugular venous narrowing was responsible for a spontaneous CSF leak which resolved after stenting.…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative lumbar drainage has been shown to be useful in preventing CSF leak after retrosigmoid approach. (22) Laing and Moffat (23) showed that intracranial CSF pressure rises immediately after posterior fossa surgery and normalizes after 48 hours, with impaired cerebrospinal fluid absorption theorized to be the cause. Elevation in CSF pressure can result in CSF egress around the tract of the ABI electrode cable into the subgaleal space, resulting in pseudomeningocele and CSF leak.…”
Section: Discussionmentioning
confidence: 99%
“…3 The authors reported that 24 hours after surgery, all patients showed a statistically significant rise in CSF pressure from normal levels with an objective decrease in the compliance of the CSF compartment. However, this CSF pressure increase completely reversed within 48 hours of surgery, and the CSF pressure fell below the preoperative level over postoperative days 2 through 6 without any medical intervention or CSF drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with basic fluid dynamics, CSF will flow from the relatively high intracranial pressure region to the relatively low-pressure regions of the eustachian tube, middle ear space, or dehiscence in the periosteal or skin incisions. 2 To characterize the intracranial CSF pressures following AN microsurgery, Laing et al 3 measured changes in CSF pressure and cerebrovascular hemodynamics following AN microsurgery in humans. All patients showed a statistically significant rise in CSF pressure from normal levels with complete reversal within 48 hours of surgery.…”
Section: Introductionmentioning
confidence: 99%